PENGEMBANGAN PERANGKAT PEMBELAJARAN KIMIA MODEL DIRECTED ACTIVITIES RELATED TO TEXT BERBASIS LKS NON EKSPERIMEN PADA MATERI SISTEM KOLOID DI KELAS XI IPA SMA NEGERI 8 PALU - Ridwan, Ridwan (JSTT, 2014)
This is a research and development (R & D) with limited trials which aimed to develop chemistry learning tools with Directed Activities Related to Text (DARTs) model of non-experiment student worksheet-based on colloid system, which included teaching materials, student guide, teacher guide, lesson plans, student worksheet, achievement test. The subjects were the year XI sciences students of SMA Negeri 8 Palu whichwere 30 students in total. The development procedure used in this research was directed activities related to text (DARTs) instructional model based on â€œThiagarajanâ€ model or 4-D model which composed ofÂ  four stage: define, design, develop, and disseminate stages. Chemistry learning tools directed activities related to text (DARTs) model of non-experiment student worksheet-based have been developed, validated, and revised twice in order to obtain maximal results and feasible to use. Based on data analysis, it has been produced effective and feasible chemistry learning tools with directed activities related to text (DARTs) model of non-experiment student worksheet-based on colloid system instruction at the year XI sciences students of SMA Negeri 8 Palu dealing with the teahing materials, student guide, teacher guide, lesson plan, student worksheet, achievement test. The effectiveness was revealed from the indicator limited trials on chemistry learning tools directed activities related to text (DARTs) model which showed thant: (a) average studentâ€™ score on achievement test were from 72.18Â  up to 82.76 on the 100 ideal scale base. Next, 28 out of 30 students were completed or 93.3376% satisfied individual completeness which showed that classical completeness accomplished, (b) all observed studentsâ€™ active categories satisfied the entire limited criteria of determined student active effeciveness which was categorized as effective, (c) in general, students positively responded and gave highly enthusiasm towards learning tools applied in the instruction, (d) teacherâ€™ ability degree in managing chemistry instuction directed activities related to text (DARTs) model was categorized very good which was 3.53 in average, that means teacherâ€™ performance was maintained.Â